PANCHAGAVYA GRITHA – A PROMISING DRUG IN AYURVEDIC PSYCHIATRY - Jithesh, M (Asian Journal of Pharmaceutical Research and Development, 2013)
Psychiatry or Bhootavidya is one of the eight speciality branches in Ayurveda. The functions of the mind with its abnormalities have been effectively discussed in this Ancient science. Many a disease explained in modern psychiatry are well discussed under the umberella term “Unmada” in Ayurveda. The various psychiatric problems have been approached with not only medicine, but also scientific procedures like counselling and psychotherapy. This area has been termed as ‘Satwapachaya chikitsa, the preliminary form of modern psychotherapy. Ayurvedic parlance is really a treasure of several therapeutic combinations advisable in Psychiatric conditions. Of the many drugs mentioned in the management of psychiatric disorders, Panchagavya gritha is the commonly used one. Many of the combinations are in the form of gritha or medicated ghee. Several drugs are being handled on in clinical practise with positive claims. Panchagavya gritha is mentioned in the management of Apasmara or epileptic syndrome. In clinical practise, the drug seems effective in conditions like schizophrenia, Depression, Attention deficit Hyperactivity disorder, types of epilepsies, post traumatic dementia etc. This paper is an attempt to study the drug, Panchagavya gritha in detail. The constituents of the yoga have been separately assessed for their characteristics and pharmacological action. A few studies conducted in our institute are also showing promising results. The details of the study are also discussed here. The mode of action of the Panchagavya gritha is also being tried to explain in an Ayurvedic manner. It was observed that Panchagavya gritha is effective in conditions like schizophrenia, cognition in Autism, OCD in the improving the quality of life.